DHYĀNA: SOTERIOLOGICAL GNOSIOLOGY IN THE TEXTS OF HAṬHAYOGA - Danylov, D. (Bulletin of Taras Shevchenko National University of Kyiv. Philosophy, 2018)
Dhyāna in the period of haṭhayoga acquires new shades of meaning and changes its significance. The texts clearly articulate the opportunity to practice dhyāna, regardless of belonging to different religious and philosophical trends in India. Dhyāna acquires a new direction, paving the way for the understanding of the hidden knowledge about the body. The practitioner of dhyāna acquires the ability to attain "true understanding", revealing the psychological potencies that are deeply embedded in the human mind and hidden there. In "Amanaska Yoga" indicates the rejection of the stereotypical understanding. of dhyāna and its objects. One of the new meanings that dhyāna acquires during this period is "gazing at" (DTYS). The gnosiology of dhyāna during this period consists in a deep knowledge of the physical and metaphysical body, as well as in the comprehension of the metaphysical space in which it dwells. Only when such a gnosis becomes natural for a practitioner can one be considered of mastering dhyāna. The resulting knowledge, in its turn, leads to liberation.